The Effectiveness of Trunk and Balance Warm-up Exercises in Prevention, Severity, and Length of Limitation From Overuse and Acute Lower Limb Injuries in Male Volleyball Players - Yuki Muramoto; Hironobu Kuruma (North American Sports Medicine Institute, 2022)
# Background Injuries in volleyball players are most common in the ankles and knees. Many volleyball players suffer from overuse injuries because of the strain placed on the lower extremities from repeated jumping. A characteristic of players who are most at risk for lower extremity injuries is the tendency to display trunk instability during landing, such as lateral flexion and rotation. Research has shown the effectiveness of exercise-based warm-up interventions for acute volleyball injuries. However, comprehensive analyses on the use of lower extremity, trunk, and balance programs to prevent overuse injuries are lacking. # Purpose To examine the effects of trunk and balance warm-up exercises on the prevention, severity, and length of limitation of overuse and acute lower limb injuries in male volleyball players. # Study Design Prospective, single-cohort study. # Methods This study involved the 2019 (control group) and 2021 (intervention group) male volleyball teams. The control and intervention groups were on the same team; however, seven players joined in 2021 through a sports referral program through which different players are recruited. Measurements included injury incidence rate, injury severity, and injury burden. The intervention involved the addition of trunk and balance exercises during the 2021 season. # Results There was no significant difference in injury incidence rates between groups. Injury severity decreased by 3.7 days for overuse injuries (p=0.04). Injury burden decreased by 11.8 (days/1000 player hours) overall and by 7.1 (days/1000 player hours) for overuse injuries. # Conclusion The results show that an exercise-based warm-up aimed at improving trunk posture during landing did not reduce the incidence rate of injury in men's volleyball. However, the addition of this warm-up did significantly reduce the severity of overuse injury. # Level of Evidence Level 3B